Statistics & Risk Modeling : with Applications in Finance and Insurance (De Gruyter (A), 1982)
Statistics & Risk Modeling publishes articles that discuss modern methods of statistics and probabilistic modeling and their applications to risk management in finance, insurance, and related areas. It also welcomes papers that present methodological innovations in statistical theory as well as papers on innovative statistical modeling applications and inference in risk management.